2022
DOI: 10.55708/js0101005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Curcuma longa Rhizome and Tectona grandis Leaves Extracts as Green Indicators versus some Synthetic Indictors in Acid-Base Titration

Abstract: The work considered comparative analysis of CRI (Curcuma longa rhizome extract indicator) and TLI (Tectona grandis leaves extract indicator) as green indicators versus some synthetic indicators in acid -base titration involving HCl-NaOH, CH3COOH-NaOH, CH3COOH -NH4OH, and HCl-NH4OH. The codes used were SA (strong acid), SB (strong base), WA (weak acid) and WB (weak base). 10 mL of the base with three drops of the CRI, TLI, MO (methyl orange), and PL (phenolphthalein) were used. Prior to the titrations, the extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…[13][14][15] PSPP has been widely used as a smart food packaging system, [16][17][18][19][20] but as titration indicator for acid-base titration, it has not been widely used. [21][22][23][24] Its use as an indicator for acid-base titrations in chemistry experiments is also not common. 8,25 In various studies that have been reported, the solvent for extracting the pigment of PSP is methanol or ethanol of analysis grade; not many reports have used methanol or ethanol of medical grade or other grades.…”
mentioning
confidence: 99%
“…[13][14][15] PSPP has been widely used as a smart food packaging system, [16][17][18][19][20] but as titration indicator for acid-base titration, it has not been widely used. [21][22][23][24] Its use as an indicator for acid-base titrations in chemistry experiments is also not common. 8,25 In various studies that have been reported, the solvent for extracting the pigment of PSP is methanol or ethanol of analysis grade; not many reports have used methanol or ethanol of medical grade or other grades.…”
mentioning
confidence: 99%